Moringa oleifera Leaf Petroleum Ether Extract Inhibits Lipogenesis by Activating the AMPK Signaling Pathway - Xie, Jing; Wang, Yan; Jiang, Wei-Wei; Luo, Xuan-Fei; Dai, Tian-Yi; Peng, Lei; Song, Shuang; Li, Ling-Fei; Tao, Liang; Shi, Chong-Ying; Hao, Ruo-Shi; Xiao, Rong; et al. (Frontiers in Pharmacology, 2018)
In recent years, obesity has become a key factor affecting human health. Moringa oleifera. Lam is a perennial tropical deciduous tree, which is widely used in human medicine due to its nutritional and unique medicinal value. It has a cholesterol-lowering effect, but its mechanism of action is unclear. In this study, we elucidated the inhibitory effect of M. oleifera leaf petroleum ether extract (MOPEE) on lipid accumulation by in vitro and in vivo experiments, and we described its mechanism of action. MOPEE suppressed adipogenesis in 3T3-L1 adipocytes in a dose-dependent manner and had no effect on cell viability at doses up to 400 ug/mL. Furthermore, MOPEE (400 ug/mL) significantly down-regulated the expression of adipogenesis-associated proteins (peroxisome proliferator-activated receptor γ [PPARγ], CCAAT/enhancer-binding proteins α and β [C/EBPα and C/EBPβ], and fatty acid synthase [FAS]) and up-regulated the expression of a lipolysis-associated protein (hormone-sensitive lipase [HSL]) in 3T3-L1 adipocytes. Additionally, MOPEE (400 ug/mL) significantly increased the degree of phosphorylation of AMP-activated protein kinase α (AMPKα) and acetyl-CoA carboxylase (ACC). An AMPK inhibitor reversed the MOPEE-induced activation of AMPKα and ACC in 3T3-L1 adipocytes. Animal experiments showed that, in high-fat diet (HFD) mice, MOPEE (0.5 g/kg body weight [BW]) effectively decreased BW, relative epididymal, perirenal, and mesenteric fat weight and fat tissue size, and hepatic fat accumulation. Furthermore, MOPEE markedly reduced the serum levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and aspartate aminotransferase (AST). Moreover, MOPEE significantly down-regulated the expression of adipogenesis-associated proteins (PPARγ and FAS) and up-regulated the expression of a lipolysis-associated protein (adipose triglyceride lipase [ATGL]) in HFD mice hepatic and epididymal fat tissue. Additionally, MOPEE markedly increased the degree of phosphorylation of AMPKα and ACC in HFD mice hepatic and epididymal fat tissue. Following ultra-high-performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UPLC-QTOF-MS/MS) analysis, three phytocompounds (isoquercitrin, chrysin-7-glucoside, and quercitrin) were identified as compounds with relatively high levels in MOPEE. Among them, quercitrin showed excellent fat-accumulation inhibitory activity, and the three compounds had synergistic effects in inhibiting adipogenesis. Taken together, MOPEE inhibits fat accumulation by inhibiting adipogenesis and promoting lipolysis, and this process is related to AMPK activation.